2016
DOI: 10.1016/j.respol.2015.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Innovation and firm growth: Does firm age play a role?

Abstract: This paper explores the relationship between firm growth, innovation and firm age. We hypothesize that young firms undertake riskier innovation activities and are more oriented towards employment growth than towards harvesting returns in the form of sales growth. Using an extensive sample of Community Innovation Survey for the period 2004-2010, we apply quantile regressions and a Heckman sample selection technique to study the impact of R&D activities on firm growth according to firm age. Our results show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
415
4
37

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 655 publications
(490 citation statements)
references
References 88 publications
34
415
4
37
Order By: Relevance
“…For example, new companies usually face high costs of experimentation and they must provide training to new R&D employees. Older companies, in contrast, are more efficient at introducing process innovations as they have the financial backing entailed by uncertain mid-term returns characterising innovation, and they tend to prefer exploitation over exploration (Coad et al 2016). As such, young born green companies entering markets with their innovative products and services are likely to face significantly different innovation challenges compared to the more established firms that adopt environmentally friendly innovations as a reaction to the changing industry landscape.…”
Section: The Green Industry and Corporate Life Cyclementioning
confidence: 99%
See 1 more Smart Citation
“…For example, new companies usually face high costs of experimentation and they must provide training to new R&D employees. Older companies, in contrast, are more efficient at introducing process innovations as they have the financial backing entailed by uncertain mid-term returns characterising innovation, and they tend to prefer exploitation over exploration (Coad et al 2016). As such, young born green companies entering markets with their innovative products and services are likely to face significantly different innovation challenges compared to the more established firms that adopt environmentally friendly innovations as a reaction to the changing industry landscape.…”
Section: The Green Industry and Corporate Life Cyclementioning
confidence: 99%
“…Unlike their more established and larger counterparts, these new organisations take time to understand sustainability and feasibility before rapidly developing into lucrative and technologically challenging niche green areas. Start-ups within green initiatives are therefore better poised to benefit from radical innovations building on breakthrough eco-technologies, and, at the same time, to internalise negative externalities, regulatory challenges and compliance costs by factoring these into economic decisions upfront and, thus, achieving faster growth and enhanced competitiveness (Ács and Audretsch 1990;Coad et al 2016;Porter and van der Linde 1995). Yet, most of the literature is still limited to the remits of more established firms, leaving gaps in the understanding of green entrepreneurial firms and their activities.…”
Section: The Green Industry and Corporate Life Cyclementioning
confidence: 99%
“…Dutta et al (1999) and Nath et al (2010) found that OCAP correlated positively with the proclivity for the defender strategy. The fourth control variable, Age (AGE), is the number of years a company had been operating, which correlated inversely with the prospector and defender strategies (Cucculelli, 2014;Coad et al, 2016). Fifth, firm size (SIZE), measured using a natural logarithm of total assets, indicated that a bigger firm size implied more resources and greater capabilities, thus the organization was better structured and would tend to focus on either a prospector or defender strategy; not a hybrid strategy (analyzer).…”
Section: Control Variablesmentioning
confidence: 99%
“…They use firm age as a moderator of R&D's impact on knowledge creation. Coad et al (2016) explore the relationship between innovation and firm growth for firms of different ages showing that young firms face larger performance benefits from R&D at the upper quantiles of the growth rate distribution, but face larger decline at the lower quantiles. They also conclude that R&D investment by young firms appears to be significantly riskier than R&D investment made by mature firms.…”
Section: Literature Reviewmentioning
confidence: 99%